Getting to grips with wildlife research by citizen scientists: what role for regulation? - Palmer, A; Reynolds, SJ; Lane, J; Dickey, R; Greenhough, B (Wiley, 2020)
1. Wildlife research by citizen scientists involving capture and handling of animals provides clear scientific benefits, but also potential risks to animal welfare. We explore debates about how best to regulate such work to ensure that it is undertaken in an ethical manner. 2. We focus on the UK as a case study, drawing on qualitative research and stakeholder engagement events. We show that because trapping and marking of certain species requires minimal licensing, training, and justification, some argue for increased formal regulation to minimise risks to animal welfare. However, others have reflected on the already complex regulatory landscape affecting wildlife research, and have expressed concern that introducing additional formal regulations could potentially make citizen science working with wildlife more difficult. Informal regulation could therefore offer a preferable alternative. 3. We set out three steps that could be taken to open up conversations about ethics and regulation of wildlife-focussed citizen science, in the UK and elsewhere: a) take stock of wildlife-focussed citizen science in terms of numbers and harms to animal welfare; b) assess the state of formal regulations and consider reforms; and c) consider informal regulations as alternatives or additions to formal regulations.